Preparation method and application of supported bimetal (Zn, Fe)-TCPP photosensitive catalyst
By using porphyrin-based bimetallic MOFs material and porous support solid-load technology in inorganic semiconductor photocatalysts, the problems of low visible light absorption and insignificant catalytic effect in inorganic semiconductor photocatalysts are solved, and efficient photocatalytic and rapid solid-liquid separation are achieved, avoiding secondary pollution of water.
Patent Information
- Application Number
- CN202411848657.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-14
AI Technical Summary
The existing inorganic semiconductor photocatalysts have low visible light absorption and insignificant catalytic effect. At the same time, the loss rate of powder materials in circulation and recovery is large, resulting in secondary pollution of water.
Using porphyrin-based bimetallic MOFs material, a regular structure (Zn,Fe)-TCPP bimetallic MOFs material is synthesized under the solvothermal method through a template agent, and it is solidly supported on a porous support. The large skeleton structure of the porphyrin-based ligand and the synergistic effect between the bimetallics is used to promote photocurrent response and electron-hole separation.
It significantly improves the photocatalytic efficiency, realizes rapid solid-liquid separation and material recycling, avoids secondary pollution of water, and improves the stability and recycling value of the catalyst.
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method and application of a supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst, which utilizes the porphyrin-based bimetallic MOFs skeleton structure characteristics to promote light absorption and carrier migration, and further solidifies to achieve rapid solid-liquid separation, while accelerating the photocatalytic degradation efficiency, and is used in the field of sewage treatment. Background Art
[0002] Photocatalysts can generate holes and electrons under light irradiation and have redox ability under light conditions. Photocatalysts can convert solar energy into energy substances, and can also promote the degradation of pollutants or the synthesis of substances. Therefore, photocatalysis is considered to be a promising way to solve the energy crisis and environmental pollution.
[0003] Inorganic semiconductor photocatalysts have excellent photocatalytic efficiency and have been widely used in the field of photocatalysis. However, due to the wide band gap and low visible light absorption efficiency, the effect of photocatalytic degradation of pollutants is still not ideal. MOFs is a porous material with a periodic network structure that can be assembled by the coordination of organic ligands and metal centers. MOFs materials have high specific surface area and rich porosity, and their structure and performance are adjustable. They are widely used in adsorption, catalysis and other fields. Compared with traditional inorganic photocatalysts, there are a large number of catalytic active sites in MOFs materials, and their open channels are used for electron transfer. Among the many MOFs materials, porphyrin metal organic frameworks contain visible light active porphyrin ligands. Porphyrins can be excited at specific wavelengths as photosensitizers and can produce a large amount of active oxygen, which is conducive to the improvement of the catalytic reaction rate. However, MOFs materials have poor water stability, and the metal active centers are easy to fall off, causing secondary pollution of water bodies.
[0004] Bimetallic nanoscale metal-organic frameworks are assembled from two different inorganic metal ions / clusters and organic ligands and are a new generation of nanoscale porous materials. Compared with monometallic MOFs, bimetallic MOFs not only have the advantages of adjustable porosity, large specific surface area, and diverse functions, but also have synergistic effects and enhanced performance, including stable structure and catalytic selectivity.
[0005] Based on this, the patent application utilizes the large conjugated π-electron system of the porphyrin-based ligand to enhance the photocatalytic activity through non-covalent interactions such as π-π stacking, hydrogen bonding or electrostatic interactions, and utilizes the synergistic effect between bimetallic groups to improve the structural stability and photochemical stability of the material. At the same time, the active components are immobilized on a porous carrier, which is conducive to high loading of catalytic sites, efficient mass transfer and strong visible light absorption, and can enable the supported material to be quickly separated from water, solving the problem of complex recovery and high loss of powder materials. Summary of the invention
[0006] In view of the problems that conventional inorganic semiconductor photocatalysts have low visible light absorption rate, insignificant catalytic effect and high loss rate of powder materials during recycling, a template agent is used to further guide the morphology and structure of porphyrin-based bimetallic MOFs materials, construct a structurally regular MOFs material, improve the photocatalytic efficiency, and further achieve rapid solid-liquid separation through immobilization treatment. The purpose of the present invention is to provide a method for preparing a supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst.
[0007] Another object of the present invention is to provide a supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst product prepared by the above method.
[0008] Another object of the present invention is to provide an application of the above product.
[0009] The object of the present invention is achieved by the following scheme: a preparation method and application of a supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst, characterized in that the metal porphyrin ligand is used to regulate the microenvironment of MOF and the synergistic effect between the conjugated ligand of MOF and the metal center Zn and Fe, so as to enhance the photocurrent response and accelerate the separation and transfer of photogenerated electrons and holes, and specifically comprises the following steps: (1) Under magnetic stirring, a certain amount of FeCl 3 6H 2 O、ZnCl 2 6H 2 O and tetraphenylporphyrin (TCPP) were dispersed in DMF solvent, 0.01 g of cetylpyridinium bromide was added, and then the tetraphenylporphyrin solution was slowly added dropwise to the metal mixed solution and then ultrasonically dispersed for 20 min; (2) transferring the mixed solution in (1) into a polytetrafluoroethylene reactor, and then adjusting the reaction temperature and time; (3) The obtained product is centrifuged, washed and dried in an oven at 60°C to obtain bimetallic (Zn,Fe)-TCPP; (4) Weigh (Zn,Fe)-TCPP and carrier according to a certain mass ratio, disperse (Zn,Fe)-TCPP in ethanol, mix and stir, and after dispersion is complete, place the carrier in the dispersed solution and place it on a constant temperature shaker for shaking and mixing, controlling the temperature, rate and time; (5) After the adsorption is saturated, the process is repeated several times, and finally the loaded (Zn, Fe)-TCPP material is dried.
[0010] The molar ratio of nFe:nZn:nTCPP is 2:(1-5):1; The reaction temperature is 90-140°C and 2-6h; The carrier is any one of porous polyurethane foam, nickel foam, and activated alumina beads, and the mass ratio of (Zn, Fe)-TCPP to the carrier is 1: (10-30); The shaking reaction temperature, rate and time are 25-60°C, 100-200 r / min and 2-4 h respectively, and the shaking mixing times are 1-3 times.
[0011] The present invention provides a supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst, which is characterized in that it is prepared according to any of the above methods.
[0012] The invention provides application of a supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst in catalytic degradation of bisphenol A.
[0013] The photocatalytic performance test of the loaded (Zn,Fe)-TCPP photosensitive catalyst was carried out in a beaker. 50g of the catalyst was added to 500mL of 100mg / L bisphenol A solution. After dark treatment for adsorption and desorption equilibrium, a 300W Xe lamp was turned on for illumination. Samples were taken every 15min and illuminated for 2h. The supernatant was taken by centrifugation to determine the degradation efficiency of bisphenol A.
[0014] By utilizing the large skeleton structure of the porphyrin-based ligand, a unique charge transfer pathway is constructed, which promotes the separation of photogenerated electrons and holes and the extensive visible light absorption. In addition, the synergistic effect between the bimetallic Zn and Fe can further promote the transfer of charges, which is beneficial to the improvement of photocatalytic ability and the stability of the material structure. On this basis, further immobilizing it on a porous carrier can not only enhance the contact area with pollutants, but also the supported catalyst can be quickly separated from water, which is easy to recycle and reuse, avoiding the problem of secondary water pollution caused by the difficulty of recycling powder catalysts. The products derived from this preparation technology have the value of large-scale application.
[0015] The present invention has the following advantages: (1) The present invention proposes a preparation method and application of a supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst, which utilizes the structural advantages of the large skeleton and specific surface area of the porphyrin-based ligand and uses a structure-directing agent to synthesize a supported, structured (Zn, Fe)-TCPP bimetallic MOFs material under a solvothermal method. The synergistic effect between Zn / Fe and organic ligands effectively constructs a unique charge transfer path, accelerating the separation efficiency of photogenerated electrons and holes under visible light. At the same time, the porous carrier can accelerate the contact area between the pollutant and the adsorption and precipitation material, which is beneficial to adsorption and catalytic degradation.
[0016] (2) The loaded (Zn, Fe)-TCPP photosensitive catalyst proposed in the present invention can achieve rapid solid-liquid separation, and the porous carrier can be regenerated by flushing and can be recycled. It has good stability and has potential application prospects in the field of environmental governance.
[0017] (3) The preparation method of the supported (Zn,Fe)-TCPP photosensitive catalyst proposed in the present invention is not only simple and controllable, but also has rich pore structure, large specific surface area, and high adsorption capacity, which can effectively prolong the lifetime of photogenerated carriers and enhance the catalytic efficiency. DETAILED DESCRIPTION
[0018] The present invention is further described by way of examples.
[0019] Embodiment 1: A supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst utilizes metalloporphyrin ligands to regulate the microenvironment of MOF and the synergistic effect between the conjugated ligands of MOF and the metal centers Zn and Fe to enhance the photocurrent response and accelerate the separation and transfer of photogenerated electrons and holes. The preparation is carried out according to the following steps: (1) Under magnetic stirring, FeCl 3 6H 2 O、ZnCl 2 6H 2 O and tetraphenylporphyrin (TCPP) were dispersed in DMF solvent respectively, 0.01 g of hexadecylpyridinium bromide was added thereto, and then the tetraphenylporphyrin solution was slowly added dropwise to the metal mixed solution, and ultrasonically dispersed for 20 min to obtain a mixed solution; (2) The mixed solution in (1) was transferred into a polytetrafluoroethylene reactor, and then reacted at 100° C. for 5 h to obtain a precipitated product; (3) The obtained product is centrifuged, washed and dried in an oven at 60°C to obtain bimetallic (Zn,Fe)-TCPP; (4) Weigh (Zn,Fe)-TCPP and porous polyurethane foam carrier according to the mass ratio of (Zn,Fe)-TCPP to porous polyurethane foam of 1:10, disperse (Zn,Fe)-TCPP in ethanol, mix and stir, and after dispersion is complete, place the carrier in the dispersed solution, place it on a constant temperature shaker at 25°C for mixing, and shake at a rate of 150 r / min for 2 h; (5) After adsorption is saturated, repeat the process twice, and finally dry the loaded (Zn,Fe)-TCPP material.
[0020] The catalytic degradation efficiency of the prepared photosensitive catalyst for bisphenol A is 89.5%.
[0021] Embodiment 2: A supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst, step (1) is the same as in Example 1, and is prepared according to the following steps: (1) Under magnetic stirring, FeCl 3 6H 2 O、ZnCl 2 6H 2 O and tetraphenylporphyrin (TCPP) were dispersed in DMF solvent, 0.01 g of cetylpyridinium bromide was added, and then the tetraphenylporphyrin solution was slowly added dropwise to the metal mixed solution and then ultrasonically dispersed for 20 min; (2) The mixed solution in (1) was transferred to a polytetrafluoroethylene reactor, and then reacted at 120° C. for 4 h to obtain a precipitated product; (3) The obtained product is centrifuged, washed and dried in an oven at 60°C to obtain bimetallic (Zn,Fe)-TCPP; (4) Weigh (Zn,Fe)-TCPP and activated alumina support in a mass ratio of 1:30, disperse (Zn,Fe)-TCPP in ethanol, mix and stir, and after dispersion is complete, place the support in the dispersed solution, place it on a constant temperature shaker at 30°C for mixing, and shake at 200 r / min for 2 h; (5) After adsorption is saturated, repeat the process three times and finally dry the loaded (Zn,Fe)-TCPP material.
[0022] The catalytic degradation efficiency of the prepared photosensitive catalyst for bisphenol A is 96.2%.
[0023] Embodiment 3: A supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst is prepared according to the following steps: (1) Under magnetic stirring, FeCl 3 6H 2 O、ZnCl 2 6H 2 O and tetraphenylporphyrin (TCPP) were dispersed in DMF solvent, 0.01 g of cetylpyridinium bromide was added, and then the tetraphenylporphyrin solution was slowly added dropwise to the metal mixed solution and then ultrasonically dispersed for 20 min; (2) The mixed solution in (1) was transferred to a polytetrafluoroethylene reactor, and then reacted at 140° C. for 4 h to obtain a precipitated product; (3) The obtained product is centrifuged, washed and dried in an oven at 60°C to obtain bimetallic (Zn,Fe)-TCPP; (4) Weigh (Zn,Fe)-TCPP and porous polyurethane foam carrier according to the mass ratio of (Zn,Fe)-TCPP to porous polyurethane foam of 1:20, disperse (Zn,Fe)-TCPP in ethanol, mix and stir, and after dispersion is complete, place the carrier in the dispersed solution, place it on a constant temperature shaker at 25°C for mixing, and shake at a rate of 100 r / min for 2 h; (5) After adsorption is saturated, repeat the process twice, and finally dry the loaded (Zn,Fe)-TCPP material.
[0024] The catalytic degradation efficiency of the prepared photosensitive catalyst for bisphenol A is 93.7%.
[0025] Embodiment 4: A supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst is prepared according to the following steps: (1) Under magnetic stirring, FeCl 3 6H 2 O、ZnCl 2 6H 2 O and tetraphenylporphyrin (TCPP) were dispersed in DMF solvent, 0.01 g of cetylpyridinium bromide was added, and then the tetraphenylporphyrin solution was slowly added dropwise to the metal mixed solution and then ultrasonically dispersed for 20 min; (2) The mixed solution in (1) was transferred to a polytetrafluoroethylene reactor, and then reacted at 120° C. for 2 h to obtain a precipitated product; (3) The obtained product is centrifuged, washed and dried in an oven at 60°C to obtain bimetallic (Zn,Fe)-TCPP; (4) Weigh (Zn,Fe)-TCPP and porous polyurethane foam carrier according to the mass ratio of (Zn,Fe)-TCPP to porous polyurethane foam of 1:10, disperse (Zn,Fe)-TCPP in ethanol, mix and stir, and after dispersion is complete, place the carrier in the dispersed solution, place it on a constant temperature shaker at 40°C for mixing, and shake at a rate of 150 r / min for 2 h; (5) After the adsorption is saturated, repeat once, and finally dry the loaded (Zn,Fe)-TCPP material.
[0026] The catalytic degradation efficiency of the prepared photosensitive catalyst for bisphenol A is 90.1%.
Claims
1. A method for preparing a supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst, characterized in that: The metal porphyrin ligand is used to regulate the microenvironment of MOF and the synergistic effect between the conjugated ligand of MOF and the metal center Zn and Fe to enhance the photocurrent response and accelerate the separation and transfer of photogenerated electrons and holes, including the following steps: (1) Under magnetic stirring, FeCl3·6H2O, ZnCl2·6H2O and tetraphenylporphyrin (TCPP) were dispersed in DMF solvent according to the molar ratio of nFe:nZn:nTCPP of 2:(1-5):1, 0.01 g of hexadecylpyridine bromide was added thereto, and then the tetraphenylporphyrin solution was slowly added dropwise to the metal mixed solution and then ultrasonically dispersed for 20 min to obtain a mixed solution; (2) Transfer the mixed solution in (1) to a polytetrafluoroethylene reactor and react at 90-140° C. for 2-6 hours to obtain a precipitated product; (3) The obtained product is centrifuged, washed and dried in an oven at 60°C to obtain bimetallic (Zn,Fe)-TCPP; (4) Disperse (Zn,Fe)-TCPP in ethanol at a ratio of (Zn,Fe)-TCPP to carrier of 1:(10-30), mix and stir, and after dispersion is complete, place the carrier in the dispersion solution and place it on a constant temperature shaker at 25-60°C for shaking and mixing; (5) After adsorption is saturated, the process is repeated several times, and the loaded (Zn, Fe)-TCPP material is obtained after drying.
2. A method for preparing a supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst according to claim 1, characterized in that: The carrier is any one of porous polyurethane foam, nickel foam and activated alumina beads.
3. The method for preparing a supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst according to claim 1, characterized in that In the shaking reaction, the shaking rate is 100-200 r / min for 2-4 h, and the shaking mixing times are 1-3 times.
4. A method for preparing a supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst according to any one of claims 1 to 3, characterized in that In, prepare according to the following steps: (1) Under magnetic stirring, FeCl3·6H2O, ZnCl2·6H2O and tetraphenylporphyrin (TCPP) were dispersed in DMF solvent at a molar ratio of nFe:nZn:nTCPP of 2:5:1, 0.01 g of hexadecylpyridinium bromide was added thereto, and then the tetraphenylporphyrin solution was slowly added dropwise to the metal mixed solution, and ultrasonic dispersion was performed for 20 min to obtain a mixed solution; (2) The mixed solution in (1) was transferred into a polytetrafluoroethylene reactor, and then reacted at 100° C. for 5 h to obtain a precipitated product; (3) The obtained product is centrifuged, washed and dried in an oven at 60°C to obtain bimetallic (Zn,Fe)-TCPP; (4) Weigh (Zn,Fe)-TCPP and porous polyurethane foam carrier according to the mass ratio of (Zn,Fe)-TCPP to porous polyurethane foam of 1:10, disperse (Zn,Fe)-TCPP in ethanol, mix and stir, and after dispersion is complete, place the carrier in the dispersed solution, place it on a constant temperature shaker at 25°C for mixing, and shake at a rate of 150 r / min for 2 h; (5) After adsorption is saturated, repeat the process twice, and finally dry the loaded (Zn,Fe)-TCPP material.
5. A method for preparing a supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst according to any one of claims 1 to 3, characterized in that The preparation was carried out according to the following steps: (1) under magnetic stirring, FeCl3·6H2O, ZnCl2·6H2O and tetraphenylporphyrin (TCPP) were dispersed in DMF solvent according to the molar ratio of nFe:nZn:nTCPP of 2:5:1, 0.01 g of hexadecylpyridinium bromide was added thereto, and then the tetraphenylporphyrin solution was slowly added dropwise to the metal mixed solution and then ultrasonically dispersed for 20 min; (2) The mixed solution in (1) was transferred to a polytetrafluoroethylene reactor, and then reacted at 120° C. for 4 h to obtain a precipitated product; (3) The obtained product is centrifuged, washed and dried in an oven at 60°C to obtain bimetallic (Zn,Fe)-TCPP; (4) Weigh (Zn,Fe)-TCPP and activated alumina support in a mass ratio of 1:30, disperse (Zn,Fe)-TCPP in ethanol, mix and stir, and after dispersion is complete, place the support in the dispersed solution, place it on a constant temperature shaker at 30°C for mixing, and shake at 200 r / min for 2 h; (5) After adsorption is saturated, repeat the process three times and finally dry the loaded (Zn,Fe)-TCPP material.
6. A method for preparing a supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst according to any one of claims 1 to 3, characterized in that The preparation was carried out according to the following steps: (1) under magnetic stirring, FeCl3·6H2O, ZnCl2·6H2O and tetraphenylporphyrin (TCPP) were dispersed in DMF solvent at a molar ratio of nFe:nZn:nTCPP of 2:2:1, 0.01 g of hexadecylpyridinium bromide was added thereto, and then the tetraphenylporphyrin solution was slowly added dropwise to the metal mixed solution and then ultrasonically dispersed for 20 min; (2) The mixed solution in (1) was transferred to a polytetrafluoroethylene reactor, and then reacted at 140° C. for 4 h to obtain a precipitated product; (3) The obtained product is centrifuged, washed and dried in an oven at 60°C to obtain bimetallic (Zn,Fe)-TCPP; (4) Weigh (Zn,Fe)-TCPP and porous polyurethane foam carrier according to the mass ratio of (Zn,Fe)-TCPP to porous polyurethane foam of 1:20, disperse (Zn,Fe)-TCPP in ethanol, mix and stir, and after dispersion is complete, place the carrier in the dispersed solution, place it on a constant temperature shaker at 25°C for mixing, and shake at a rate of 100 r / min for 2 h; (5) After adsorption is saturated, repeat the process twice, and finally dry the loaded (Zn,Fe)-TCPP material.
7. A method for preparing a supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst according to any one of claims 1 to 3, characterized in that The preparation was carried out according to the following steps: (1) under magnetic stirring, FeCl3·6H2O, ZnCl2·6H2O and tetraphenylporphyrin (TCPP) were dispersed in DMF solvent according to the molar ratio of nFe:nZn:nTCPP of 2:1:1, 0.01 g of hexadecylpyridinium bromide was added thereto, and then the tetraphenylporphyrin solution was slowly added dropwise to the metal mixed solution and then ultrasonically dispersed for 20 min; (2) The mixed solution in (1) was transferred to a polytetrafluoroethylene reactor, and then reacted at 120° C. for 2 h to obtain a precipitated product; (3) The obtained product is centrifuged, washed and dried in an oven at 60°C to obtain bimetallic (Zn,Fe)-TCPP; (4) Weigh (Zn,Fe)-TCPP and porous polyurethane foam carrier according to the mass ratio of (Zn,Fe)-TCPP to porous polyurethane foam of 1:10, disperse (Zn,Fe)-TCPP in ethanol, mix and stir, and after dispersion is complete, place the carrier in the dispersed solution, place it on a constant temperature shaker at 40°C for mixing, and shake at a rate of 150 r / min for 2 h; (5) After the adsorption is saturated, repeat once, and finally dry the loaded (Zn,Fe)-TCPP material.
8. A supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst, characterized in that Prepared according to any one of claims 1 to 7.
9. Use of the supported bimetallic (Zn, Fe)-TCPP photosensitive catalyst according to claim 8 in the catalytic degradation of bisphenol A.